(untitled) - Jobber, David (London, 1995)
The book combines comprehensive coverage of the principles of marketing with unique emphasis on its practical implementation within Europe business. It is in five parts: 1) Fundamental of modern marketing throught summarizes core marketing pinciples including the marketing concept and marketing planning, consumer and buyer behaviour, marketing research, and segmentation and positioning. 2) Marketing mixed decision focuses upon the development of effectiuve strategies for pricing, promotion, product development and distribution. 3) Competition and marketing discusses the issues of industry attractiveness, competitive advantage and the nature of competitive behaviour. 4) Marketing implementation provides in-depth coverage of this often negleted topic. It describes the resistance that necessary change often provokes and the strategies to overcome this resistance. It also analyses the various forms of marketing organization and how each one affects how marketing strategy is implemented. 5) Marketing applications focuses upon the special characteristics of service industries and the particular issues associated with globalization. The book includes numerous learning aids including chapter objectives, chapter summaries, study questions and extensive references. There is a case study at the end of each chapter with an extended case at the end of each module
Keywords: Marketing,Marketing; Case studies; Europe